Cardiopatía congénita en prematuro, hijo de madre diabética: Reporte de caso: Congenital heart disease in premature, child of a diabetic mother: Case report - Aguirre-Sánchez, María Melanie (2022)
The baby of a diabetic mother is an infant with a high risk of presenting complications, which may be more serious in children of pregnant women diagnosed with diabetes before pregnancy and with inadequate metabolic control. In Peru, there is little information about the incidence of this problem. The case of a premature, macrosomic infant with dysmorphic syndrome, congenital heart disease and multicystic kidney, has a maternal history of type 2 diabetes mellitus, the patient presented an unfavorable clinical evolution and died. The diagnosis of a diabetic mother should be considered in pregnant women with clinical signs suggestive of the disease, since inadequate prenatal control can lead to an unfavorable prognosis in these children.